A Study on Nutrient Uptake by Crops and Weeds under Different Planting Dates and Integrated Weed Management Strategies in Soybean (Glycine max L.) - Zion, G.; Longkumer, L. T. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during (June–October, 2021 and 2022) at School of Agricultural Sciences, Medziphema Campus, Nagaland University, India, to investigate the effects of sowing dates and weed management strategies on nutrient uptake by crops and weeds in soybean (Glycine max L.) cultivation. A split-plot design was employed with three sowing dates (June 15, June 30, and July 15) and seven weed control treatments, including soil solarization, mulching, herbicides, manual weeding, and a weedy check. The results showed that early sowing on June 15 significantly reduced weed density, dry weight, and nutrient depletion by weeds compared with that on later sowing dates. Among the weed control treatments, hand weeding at 20 and 40 days after sowing (DAS) was the most effective in controlling weeds. The application of pendimethalin 30 EC at 1 kg ha-1 as pre-emergence (PE)+imazethapyr 10 SL at 100 g ha-1 as post-emergence (PoE) at 20 DAS was the best herbicidal treatment, resulting in the lowest weed count, dry weight and nutrient depletion. Nutrient uptake by soybean seed and stover was highest with the June 15 sowing date and two hand weedings, followed by the application of pendimethalin (PE)+imazethapyr application (PoE). This study emphasizes the significance of early sowing and effective weed management in maximizing the nutrient uptake, growth, and yield of soybean under the prevailing conditions in Nagaland, India.